PIN diode drive circuits optimized for fast switching - Brorsson, Christoffer (My University, 2012)
The use of RF and microwave switches based on PIN diodes is widely spread. In a radar system the switch directs transmit and receive signals to and from the antenna. In scenarios where the target is small and in close range there is a need for high output power and fast switching. But there is one fundamental problem: High power handling capability and fast switching speed are conflicting parameters in a PIN diode. In order to bridge the gap, between power handling capability and speed, the PIN diode drive circuit currently in use at SAAB has been studied. The PIN diode drivers control the biasing of the PIN diodes and thus affects the speed of the switch. Several modifications was made to the driver design. The fastest PIN diode driver is able to switch two PIN diodes with a carrier lifetime, L, of 2000ns in just 237ns. This is an improvement of 963ns over the original design. It has been proven that small changes in the driver design can improve the time response of a switch while still maintaining the same power handling capability.
Keywords: Elektroteknik och elektronik; Informations- och kommunikationsteknik; Telekommunikation; Electrical Engineering, Electronic Engineering, Information Engineering; Information & Communication Technology; Telecommunications